Education under the drug risk for Elementary School audience: the ludic as a strategy (Research, Society and Development, 2020)
This research was carried out with primary school students of a public school in a city in the country of the State of Rio Grande do Sul, Brazil, in order to reduce the risk of exposure to drugs through educational activities under conceptual, attitudinal and of self-valorization. For that, a survey of the reality of the students involved in the context of the theme was carried out through a standardized questionnaire, which guided a dialogued exposition about the main legal and illicit drugs pointed out, followed by a game with a cognitive bias. In another moment, a second game (Role Play Game) was applied to work attitudinal aspects; finally, it was proposed that they construct, through text and drawing, what they understood as an ideal neighborhood and what they could do within their reach to improve their neighborhood. When we approach the subject of drug addiction using these playful strategies, coupled with the reflexive exercise about their social context, we witness positive involvement of the students, materialized by the answers to a questionnaire applied at the end of the last meeting. We perceive a better understanding of the students about the consequences of drug use, which can corroborate to decrease their exposure to drugs.